2010
DOI: 10.1037/a0019119
|View full text |Cite
|
Sign up to set email alerts
|

Two case studies of child-centered play therapy for children referred with highly disruptive behavior.

Abstract: This article presents two cases with strong evidence measures in which child-centered play therapy (CCPT) was provided for children referred for highly disruptive behavior, including attention problems and aggression. Apparent progress was evidenced on the Teacher Report Form (TRF) of the Child Behavior Checklist (Achenbach & Rescorla, 2001). One client had a waiting period equal to his treatment period in which ratings were stable before change across his treatment period. The cases provide opportunities to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 25 publications
1
67
0
1
Order By: Relevance
“…In this study, as well as others (Cochran, Cochran, Nordling, McAdam, & Miller, 2009;Cochran, Fauth, Cochran, Spurgeon, & Pierce, in press;Demanchick et al, 2003), a therapeutic experience prompting change in self-concept or beliefs about self in relation to others seems to have been the key to changing behavior. For example, Client C often seemed to drive others away with an attitude of stern disgruntlement, outright criticism, argumentativeness, and the one-upping of others at every turn.…”
Section: Ccpt and Mechanisms Of Change: Internal Change Prompting Extsupporting
confidence: 52%
“…In this study, as well as others (Cochran, Cochran, Nordling, McAdam, & Miller, 2009;Cochran, Fauth, Cochran, Spurgeon, & Pierce, in press;Demanchick et al, 2003), a therapeutic experience prompting change in self-concept or beliefs about self in relation to others seems to have been the key to changing behavior. For example, Client C often seemed to drive others away with an attitude of stern disgruntlement, outright criticism, argumentativeness, and the one-upping of others at every turn.…”
Section: Ccpt and Mechanisms Of Change: Internal Change Prompting Extsupporting
confidence: 52%
“…Counselor genuineness, counselor consistency, nonjudgment, unconditional positive regard, and the freedom for the children to direct their play and express themselves how they choose are pertinent characteristics of a counselor using CCPT (Axline, 1969;Guerney, 1983;Landreth, 2012). CCPT has been shown to be effective in enhancing children's self-concept and emotional regulation (Cochran, Cochran, Nordling, McAdam, & Miller, 2010), reducing aggressive behaviors (Ray, Blanco, Sullivan, & Holliman, 2009), reducing attention problems (Bratton et al, 2013), lessening undesirable social behaviors (Cochran et al, 2010), decreasing externalizing behavioral problems (Bratton et al, 2013), and reducing internalizing problems (Packman & Bratton, 2003). CCPT is also effective for children with learning disabilities (Guerney, 1983), as well as children who have experienced child abuse (In & McDermott, 1976), have experienced trauma (Kuhli, 1979), and have been diagnosed with ASD (Salter, Beamish, & Davies, 2016).…”
Section: Ccptmentioning
confidence: 99%
“…It refers to an attitude or behavior that can only be expressed if the doctor is self-aware [ 28 ]. Similarly, studies have noted that doctors’ genuineness could be conceptualized as being real, being their true authentic self, and getting rid of dishonest and false behavior [ 29 ]. Nevertheless, how to concretely perceive genuineness via “self” has been understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Another study suggested that when a doctor disclosed his/her own lifestyle (e.g., positive health behaviors or daily activities), patients considered the doctor to be more credible and approachable [ 32 ]. Likewise, patients particularly valued when doctors disclosed the accumulated skills, experience, and specific expertise in the field [ 28 , 29 , 30 ]. Expanded on the previous studies, our study aims at investigating these three types of self-disclosure exhibited in the SMIP communication, and how public responded to different types of disclosure.…”
Section: Introductionmentioning
confidence: 99%